The Analysis of Word Formation in Coffee Shops’ Menus in Bintaro - Maharini, May Triranto; Nainggolan, Erni Susianti (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study  aims to find the word formation employed in coffee shop menus in Bintaro, Tangerang, Indonesia. By examining word formation processes, naming conventions, and menu item types. This research aims to understand how coffee shops effectively communicate their offerings to customers through word formation processes. It adopts a qualitative research approach, utilizing purposive sampling to select representative coffee shops in the area. Through in-person visits and online sources, menus were collected and analyzed for their linguistic features. The findings reveal that coffee shops in Bintaro utilize word formation processes. Compounding involves combining two or more words to create a new term, such as "chicken katsu" or "milkshake." Affixation, on the other hand, entails adding prefixes or suffixes to existing words, as seen in "salted" or "grilled." Blending, a more creative process, involves merging portions of two or more words to form a new word, such as "croffle" or "moccacino.". The insights gained from this research have practical implications for the readers. It is expected that the finding would show the word formation processes predominantly used in coffee shop menus in Bintaro that can be valuable for understanding how language is used to create a specific brand image. This highlights the importance of considering cultural and linguistic factors when developing menu.